Experimental and numerical investigation of deep cold rolling on Ni-based super alloy - Lee, Zi Kang (2019)
Deep Cold Rolling (DCR) is a mechanical surface treatment (MST) process whereby a hydrostatically suspended ball distorts the component surface plastically through mechanical interaction. DCR will causes formation of compressive residual stress, surface roughness reduction, and surface hardness enhancement which make DCR an ideal choice for fatigue life enhancement. The objective of this project was to develop a 3D Finite Element Method (FEM) modelling to analyse the residual stress distributions developing from the DCR process for aerospace engine components. This study was performed using the 3D commercial FEM software named ABAQUS. To investigate the effects of DCR process on the residual stress distribution of the FEM numerical model, three different method were implemented for the FEM model. Furthermore, FM-300e, a Micro Vickers hardness machine was used to analyse the micro hardness of near sub-surface region of Nickel-based Superalloy specimen after undergoing DCR process. Besides, optical microscope and Scan Electron Microscope was adopted to investigate the effect of DCR process on the microstructure of Nickel-based Superalloy specimen.